Who was Milton Bradley? - Anderson, Kirsten (Kirsten Stephanie) (Who was...?, 2016)
"Meet the man behind the board games: Milton Bradley. Born in Maine in 1836, Milton Bradley moved with his family to the working-class city of Lowell, Massachusetts, at age 11. His early life consisted of several highs and lows, from graduating high school and attending Harvard to getting laid off and losing his first wife. These experiences gave Bradley the idea for his first board game: The Checkered Game of Life. He produced and sold Life across the country and it quickly became a national sensation. Working with his company, the Milton Bradley Company, he continued to produce board games, crayons, and kid-friendly school supplies for the rest of his life. He is often credited as the father of board games, and the Milton Bradley Company has created Battleship, Jenga, Yahtzee, Trouble, and many more classic games"--